Study on Impact of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) on Renal Function in Postpartum Period (Community Based Medical Journal, 2024)
A prospective, observational study was conducted in the Department of Obstetrics & Gynaecology of Combined Military Hospital (CMH), Dhaka, Bangladesh, to assess pre-delivery and post-delivery (5 days after administration of NSAID) change in renal function by determining the serum creatinine levels in pregnant women. The study was conducted on 120 purposively selected patients attending for their delivery purpose in the selected hospital from January to June of 2022. Following the delivery, tablet Paracetamol 500 mg thrice a day for 5 days have been prescribed to all the respondents. Diclofenac Sodium 100 mg suppository twice a day up to for 3 days had been prescribed with dosage adjusted as required. Serum creatinine levels were evaluated on two time points: the day before delivery and 5 days after delivery. Compared to the day before delivery, 53.3% of the respondents showed increased level of serum creatinine 5 days after delivery. Acute kidney injury (AKI) was identified in 9.17% patients with a change more than 0.3 mg/dL from the pre-delivery report. The change in the serum creatinine level pre-delivery to post delivery was statistically significant, which was also dependent on the NSAIDs dose with a positive linear association. Though NSAIDs regarded as a safe choice for postpartum pain management, yet apparently healthy mothers showed fluctuations in serum creatinine level in association to dosage of NSAIDs use.  CBMJ 2024 July: vol. 13 no. 02 P: 141-147